Industry–university–research knowledge flow in energy subjects: evolution of network structure in collaborative photovoltaic innovations - Wuyin Yan; Hui Liu; Baijun Han (Frontiers in Energy Research, 2023)
This data report collected photovoltaic patents under the Industry-University-Research (IUR) collaborative innovation perspective. The evolution of the collaborative innovation network from 2000 to 2019 was studied. The characteristics of patent holders and overall network characteristics was analysed based on Social Network Analysis (SNA), including network size and degree, network density, and network degree centrality. The SNA results show that the network size and degree have increased significantly over time. The network density has become increasingly sparse as PV technology has developed and the number of core network members has increased. Universities and research institutions is gradually shown its clustering role in leading innovations and discipline construction. H01L is the leading knowledge domains studied by the industry, university, and research institutions. F24J and F24S were the second most frequently involved knowledge domains in each stage. Furthermore, two noteworthy knowledge domains are H02J and H02S, which are related to control and regulation of power systems. This analysis provides insights into the energy subjects and knowledge domains within collaborative innovations and education.